Opportunities for Protecting and Restoring Tropical Coastal Ecosystems by Utilizing a Physical Connectivity Approach - Gillis, Lucy G.; Jones, Clive G.; Ziegler, Alan D.; van der Wal, Daphne; Breckwoldt, Annette; Bouma, Tjeerd J. (Frontiers in Marine Science, 2017)
Effectively managing human pressures on tropical seascapes (mangrove forests, seagrass beds and coral reefs) requires innovative approaches that go beyond the ecosystem as the focal unit. Recent advances in scientific understanding of long-distance connectivity via extended ecosystem engineering effects and on-going rapid developments in monitoring and data-sharing technologies provide viable tools for novel management approaches that make use of positive across-ecosystem interactions (for example, hydrodynamics). Scientists and managers can now use this collective knowledge to develop monitoring and restoration protocols that are specialised for cross ecosystem fluxes (waves, sediments, nutrients) on a site-specific basis for connected tropical seascape (mangrove forests, seagrass beds and coral reefs).